2023
DOI: 10.1002/jrs.6558
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the LAR 12095 Martian shergottite as determined by micro‐Raman and micro‐X‐ray fluorescence spectroscopies

Abstract: In this work, the geochemical characterization of the olivine‐phyric Martian shergottite LAR 12095 was performed by using two complementary analytical techniques: micro‐Raman and micro‐energy dispersive X‐ray fluorescence spectroscopies. Thanks to this methodology, olivine, pyroxene, and ilmenite were detected as primary minerals from Mars. Maskelynite, hematite, anatase, chromite, merrillite, oxidized mackinawite, pyrrhotite, elemental sulfur, marcasite, jarosite, epsomite, and gypsum were classified as secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…A sample of another Martian shergottite meteorite (LAR 12095) was studied by Huidobro et al 8 using micro-Raman and micro-X-ray fluorescence spectroscopies. They identified olivine, pyroxene and ilmenite as primary minerals phases, while the additionally detected minerals such as maskelynite, hematite, anatase, chromite, merrillite, oxidized mackinawite, pyrrhotite, elemental sulfur, marcasite, jarosite, epsomite and gypsum were interpreted as secondary minerals, which are the products of alteration under mostly anoxic atmosphere of Mars.…”
Section: Planetary Science and Exobiologymentioning
confidence: 99%
“…A sample of another Martian shergottite meteorite (LAR 12095) was studied by Huidobro et al 8 using micro-Raman and micro-X-ray fluorescence spectroscopies. They identified olivine, pyroxene and ilmenite as primary minerals phases, while the additionally detected minerals such as maskelynite, hematite, anatase, chromite, merrillite, oxidized mackinawite, pyrrhotite, elemental sulfur, marcasite, jarosite, epsomite and gypsum were interpreted as secondary minerals, which are the products of alteration under mostly anoxic atmosphere of Mars.…”
Section: Planetary Science and Exobiologymentioning
confidence: 99%
“…Among the notable studies in this area is the analysis of the Martian meteorite Northwest Africa (NWA) 2975 through Raman spectroscopy, which identified its major minerals as pyroxenes (primarily augite, pigeonite, and enstatite) and plagioclases (mainly shocked maskelynite). 1 Another significant contribution comes from Huidobro et al, 2 who utilized two complementary analytical techniques, micro-Raman and micro-energy-dispersive X-ray fluorescence spectroscopies, for the geochemical characterization of the Martian shergottite LAR 12095. This study revealed that olivine, pyroxene, and ilmenite were the primary minerals present in this Martian meteorite.…”
Section: Introductionmentioning
confidence: 99%